2016
DOI: 10.3758/s13414-016-1175-7
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral stimuli generate different forms of inhibition of return when participants make prosaccades versus antisaccades to them

Abstract: Inhibition of return (IOR) is usually viewed as an inhibitory aftermath of visual orienting typically seen in the form of slower responses to targets presented in a previously oriented to location. As shown by Taylor and Klein (2000. Journal of Experimental Psychology: Human Perception and Performance, 26, 1639-1656), the nature of the inhibitory effects resulting from an uninformative cue seem to be contingent on the activation state of the oculomotor system. Here we contrast target discrimination performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…Chica et al, 2010), to compare the FLE/IOR between the cued and uncued locations, or to compare the FLE/IOR between prosaccade and antisaccade conditions (c.f. Redden et al, 2016). These experiments in future studies will make more comprehensive understanding about what is actually altered when IOR occurs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Chica et al, 2010), to compare the FLE/IOR between the cued and uncued locations, or to compare the FLE/IOR between prosaccade and antisaccade conditions (c.f. Redden et al, 2016). These experiments in future studies will make more comprehensive understanding about what is actually altered when IOR occurs.…”
Section: Discussionmentioning
confidence: 92%
“…On the one hand, some studies have argued that the oculomotor system pertains to some types of IOR; accordingly, a perceptual process is modulated when fixation is maintained, whereas a motoric process is modulated when eye movements are made to a cued location (Chica et al, 2010;Taylor & Klein, 2000). On the other hand, several studies have argued that the activation state of the reflexive oculomotor system controls which type of IOR is generated; accordingly, a perceptual form is generated when the system is suppressed, whereas a motoric form is generated when the system is not suppressed (Hilchey, Dohmen, Crowder, & Klein, 2016;Hilchey et al, 2014;Redden, Hilchey, & Klein, 2016; for a review, see . In either case, it has been suggested that a blocked design is not an optimal procedure to segregate these different types of IOR (Hilchey, Klein, & Ivanoff, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To provide a firm basis for comparison with the literature, we focused on studies that were previously reviewed by Redden, Hilchey, and Klein (2016). These studies, like ours, had used a discrimination task and reported both RT and accuracy for each condition.…”
Section: Discussionmentioning
confidence: 99%
“…In a variant of our study recently conducted by Hilchey, Dohmen, Crowder, and Klein (2016), ICEs were generated by pro-or anti-saccades to peripheral cues and measured with spatially congruent manual localization responses to central arrow targets (also see Redden, Hilchey, & Klein, 2016, for responses to peripheral targets). Indeed, with oculomotor activation during prosaccades, they found a robust ICE that was predominantly output based.…”
Section: Discussionmentioning
confidence: 99%